Será que a abertura ao comércio internacional reduz a pobreza? Uma investigação a nível mundial entre 2002 e 2017 - Ana Rita Rodrigues Nogueira (2021)
Globalization, including the openness to international trade, has increased substantially in the last decades aiming at fostering economic cooperation performance of countries. Although some studies and most policy makers contend that trade openness can be critical for mitigating poverty, research results are not clear cut. Theoretically, one would expect that trade openness can influence countries' poverty levels through four main mechanisms: 1) economic growth; 2) markets and competition; 3) technology, productivity and wages; and 4) government revenues. The second mechanism produces a reduction in the level of poverty, in which producers take advantage of the increase in the price of goods and access to more inputs and consumers benefit from the decrease in the price of imported goods. The rest of mechanisms are characterized by their ambiguity, introducing de concept of immiserizing growth- when economic growth causes a deterioration in the terms of trade, increasing inequalities, which is reflected in increasing poverty and showing the presence of heterogeneities-namely in the labor market. The present study aims at assessing the impact of trade openness on a large set (160) of countries in a relatively long-time span (2002-2017) considering the whole sample of countries and countries divided according to their income levels. For estimating the impact of trade openness on the poverty rate (proxied by the human poverty index), controlled by a set of other factors (FDI, human capital, economic growth, inflation rate, exchange rate and institutional quality), we will resort to the generalized method of moments, which is able to account for the endogeneity, that is, to incorporate the existence of a reciprocity between trade openness and poverty. Key words: Poverty, Openness to trade, Immiserizing growth, Generalized Method of Moments